Предмет: Алгебра, автор: halinigor

Упростить выражение!!!!!!!!!!!!!!! 1) 2 sin a sin b + cos (a+b) 2) cos^2 (pi - a) - cos^2 (pi/2 -a) Доказать тождество!!!!!!!!!!!!!!!!!!!!! 3 cos 2a + sin^2 a - cos^2 a = 2 cos 2a

Ответы

Автор ответа: hote
0
Упростить выражение: 

1)
displaystyle 2sina*sinb+cos(a+b)=2sina*sinb+cosa*cosb-sina*sinb=\\=sina*sinb+cosa*cosb=cos(a-b)

2)
displaystyle cos^2( pi -a)-cos^2( frac{ pi }{2}-a)=(cos( pi -a))^2-(cos( frac{ pi }{2}-a))^2=\\=(-cosa)^2-(sina)^2=cos^2a-sin^2a=cos2a

Доказать тождество

displaystyle 3cos2a+sin^2a-cos^2a=2cos2a\\3(cos^2a-sin^2a)+sin^2a-cos^2a=3cos^2a-3sin^2a+sin^2a-cos^2a=\\=2cos^2a-2sin^2a=2(cos^2a-sin^2a)=2cos2a
Похожие вопросы